Descentralización y derechos sociales: reflexionando en torno a la satisfacción del derecho a la educación en el marco del proceso de descentralización - Alvites Alvites, Elena (Pontificia Universidad Católica del Perú, 2015)
Historically, fundamental rights have not been perceived in their totality with the same degree of enforceability. However, with the contributionsof both the doctrine and the jurisprudence, todayall   fundamental rights, including those with social character, are considered to impose real obligations on the State.In this article, the author shows how the decentralization process has influenced in this phenomenon, with emphasis on the right to education, and presents an analysis regarding the actual situation of this right in our country based on the positive actions that are under the responsibility of the Ministry of Education and the decentralized organisms.

Históricamente, los derechos fundamentales no han sido percibidos en su totalidad con el mismogrado de exigibilidad. No obstante, con los aportesde la doctrina y la jurisprudencia, hoy se consideraque todos los derechos fundamentales, inclusive aquellos de carácter social, imponen obligaciones reales al Estado.En el presente artículo, la autora muestra cómo el proceso de descentralización ha influido en este fenómeno, con énfasis en el derecho a la educación, y plantea un análisis respecto de la situación actual de este derecho en nuestro país a partir de las acciones positivas a cargo del Ministerio de Educación y de los organismos descentralizados.
Decentralization and social rights: reflexions around the satisfaction of the right to education in the framework of the decentralization process
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01